Childhood neurodevelopment after prescription of maintenance methadone for opioid dependency in pregnancy: a systematic review and meta‐analysis. (3rd December 2018) - Monnelly, Victoria J; Hamilton, Ruth; Chappell, Francesca M; Mactier, Helen; Boardman, James P
Abstract : Aim: To systematically review and meta‐analyse studies of neurodevelopmental outcome of children born to mothers prescribed methadone in pregnancy. Method: MEDLINE, Embase, and PsycINFO were searched for studies published from 1975 to 2017 reporting neurodevelopmental outcomes in children with prenatal methadone exposure. Results: Forty‐one studies were identified (2283 participants). Eight studies were amenable to meta‐analysis: at 2 years the Mental Development Index weighted mean difference of children with prenatal methadone exposure compared with unexposed infants was −4.3 (95% confidence interval [CI] −7.24 to −1.63), and the Psychomotor Development Index weighted mean difference was −5.42 (95% CI −10.55 to −0.28). Seven studies reported behavioural scores and six found scores to be lower among methadone‐exposed children. Twelve studies reported visual outcomes: nystagmus and strabismus were common; five studies reported visual evoked potentials of which four described abnormalities. Factors that limited the quality of some studies, and introduced risk of bias, included absence of blinding, small sample size, high attrition, uncertainty about polydrug exposure, and lack of comparison group validity. Interpretation: Children born to mothers prescribed methadone in pregnancy are at risk of neurodevelopmental problems but risk of bias limits inference about harm. Research into management of opioid use disorder in pregnancy should include evaluation of childhood neurodevelopmental outcome. What this paper adds: Children born to opioid‐dependent mothers prescribed methadone are at risk of neurodevelopmental impairment. Exposed infants have lower Mental Development Index and Psychomotor Development Index scores than unexposed children. Atypical visual evoked potentials, strabismus, and nystagmus have increased prevalence. Estimates of impairment may be biased by intermediate to poor quality evidence. What this paper adds: Children born to opioid‐dependent mothers prescribed methadone are at risk of neurodevelopmental impairment. Exposed infants have lower Mental Development Index and Psychomotor Development Index scores than unexposed children. Atypical visual evoked potentials, strabismus, and nystagmus have increased prevalence. Estimates of impairment may be biased by intermediate to poor quality evidence. Editor's Choice My Editor's Choice for the July 2019 issue is this systematic review. It highlights neurodevelopmental outcomes of children who had antenatal exposure to methadone given to their mother as maintenance treatment (as well as other, less documented risk factors). The surge in opiod dependence in the USA and other countries, particularly in young adults, raises specific concerns for the children's development. This article is commented on by Skranes on page 738 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Video Podcast: https://www.youtube.com/watch?v=Ixo12Fg0FJs Resumen: Desarrollo neurológico infantil tras la prescripción de metadona de mantenimiento para el tratamiento de la dependencia de opioides durante el embarazo: revisión sistemática y meta‐análisis: Objetivo: Revisar sistemáticamente y realizar un meta‐análisis de estudios sobre el resultado del desarrollo neurológico de los niños nacidos de madres a quienes se les recetó metadona durante el embarazo. Metodología: Se realizó una búsqueda en MEDLINE, Embase, y PsycINFO de estudios publicados desde el año 1975 al 2017 que informaran sobre el resultado del desarrollo neurológico de niños que hubieran tenido exposición prenatal a la metadona. Resultados: Se identificaron 41 estudios (2283 participantes). Ocho estudios se pudieron someter al meta‐análisis: a los dos años de edad los niños con exposición prenatal a la metadona mostraron una diferencia de medias ponderada de ‐4, 3 (95% intervalo de confianza [IC] −7, 24 to −1, 63) en el Índice de Desarrollo Mental (Mental Development Index) en comparación con los niños no expuestos. En el Índice de Desarrollo Psicomotor (Psychomotor Development Index) la diferencia de medias ponderada fue −5, 42 (95% CI −10, 55 to −0, 28). 7 estudios mostraron las puntuaciones comportamentales y 6 de ellos encontraron puntuaciones más bajas entre los niños expuestos a la metadona. Doce estudios informaron sobre los resultados a nivel visual: el nistagmo y el estrabismo fueron comunes; 5 estudios informaron sobre los potenciales evocados visuales, de los cuáles cuatro describieron anormalidades. Los factores que limitaron la calidad de algunos estudios e introdujeron el riesgo de sesgo, incluyeron la ausencia de cegamiento, el pequeño tamaño de la muestra, el alto desgaste, la incertidumbre acerca de la exposición a varias drogas y la falta de validez del grupo de comparación. Interpretación: Los niños nacidos de madres a quienes se les recetó metadona durante el embarazo se encuentran en riesgo de sufrir problemas de desarrollo neurológico, pero el riesgo de sesgo limita la inferencia sobre el daño. La investigación sobre el manejo del trastorno por uso de opioides en el embarazo debe incluir la evaluación del resultado del desarrollo neurológico infantil. Resumo: Neurodesenvolvimento infantil após prescrição de metadona de manutenção para dependência de opióides na gestação: uma revisão sistemática e metanálise: Objetivo: Revisar sistematicamente e metanalisar os estudos com resultados do neurodesenvolvimento de crianças nascidas de mães que tiveram prescrição de metadona na gestação. Método: MEDLINE, Embase, e PsycINFO foram pesquisadas por estudos publicados de 1974 a 2017 relatando resultados do neurodesenvolvimento em crianças expostas a metadona no período pré‐natal. Resultados: Quarenta e um estudos foram identificados (2.283 participantes). Oito estudos foram possíveis de incluir na metanálise: aos 2 anos a diferença na média ponderada do Índice de Desenvolvimento Mental de crianças expostas a metadona pré‐natal comparadas com as não expostas foi −4, 3 (intervalo de confiança [IC a 95%] −7, 24 a −1, 63), e a diferença na média ponderada do Índice de Desenvolvimento Psicomotor foi −5, 42 (IC 95% −10, 55 a −0, 28). Sete estudos relataram escores comportamentais e seis encontraram escores menores entre crianças expostas a metadona. Doze estudos relataram resultados visuais: nistagmo e estrabismo foram comuns; cinco estudos reportaram potenciais evocados visuais, dos quais quatro descreveram anormalidades. Fatores que limitaram a qualidade de alguns estudos e introduziram risco de viéis incluíram falta de cegamento, reduzido tamanho amostral, desgaste alto, incerteza sobre exposição a outras drogas, e falta de validade por grupo de comparação. Interpretação: Crianças nascidas de mães que receberam prescrição de metadona na gestação apresentam risco para problemas neurodesenvolvimentais, mas o risco de viés limita as inferências sobre o dano. Pesquisas sobre o manejo do uso de opióides na gestação devem incluir a avaliação do resultado do neurodesenvolvimento na infância.